Optimisation of phenolic compounds and antioxidant capacity of Trigona honey and propolis using response surface methodology from fermented food products - Hagar, Abdullah; Ibrahim, Muhammad; Ahmed, Idris Adewale; Ramli, Norazsida; M. Jalil, Abbe Maleyki; Abd Rani, Nurlisa Fatihah (Universiti Putra Malaysia, 2021)
Honey and propolis are honeybee products that are becoming increasingly common as a result of their ability to improve human health. The optimal combination of honey and propolis for total phenolic content (TPC), total flavonoid content (TFC), and antioxidant capacity were analysed for Trigona honey and propolis aqueous extracts using response surface methodology and a central composite design. The effect of honey (X1: 15 - 16.5 g) and propolis (X2: 13.5 - 15 g) on the total phenolic content (TPC, Y1), total flavonoid content (TFC, Y2), antioxidant capacity (DPPH, Y3; ABTS, Y4), and FRAP (Y5) were tested. The experimental outcomes were adequately fitted into a second-order polynomial model regarding TPC (R2 = 0.9539, p = 0.0002), TFC (R2 = 0.9209, p = 0.0010), antioxidant activity (DPPH, R2 = 0.9529, p = 0.0002; ABTS, R2 = 0.9817, p < 0.0001), and FRAP (R2 = 0.9363, p = 0.0005). The optimal percentage compositions of honey and propolis were 15.26 g (50.43%) and 15 g (49.57%), respectively. The predicted results for TPC, TFC, DPPH (IC50), ABTS, and FRAP were 162.46 mg GAE/100 g, 2.29 mgQE/g, 14.52 mg/mL, 564.27 µMTE/g, and 3.56 mMTE/g, respectively. The experimental outcomes were close to the predicted results: 152.06 ± 0.55 mg GAE/100 g, 2.21 ± 0.05 mg QE/g, 13.85 ± 0.34 mg/mL, 555.22 ± 36.84 µMTE/g, and 3.71 ± 0.02 mMTE/g, respectively. It was observed that the optimal combination of honey and propolis provided the highest antioxidant yield and can be used as functional foods, cosmetics, and medical and pharmacological ingredients.